2021
DOI: 10.1051/ro/2020098
|View full text |Cite|
|
Sign up to set email alerts
|

Withdrawn: Optimal cap setting and pricing in supply chains under vertical-horizontal cooperation and cap-and-trade regulation

Abstract: The main body of competition has changed from the competition between enterprises to the competition between supply chains. The cooperation of the chain-to-chain attracts large attention from entrepreneurs and scholars in an increasingly competitive environment. Thus, this paper studies a chain-to-chain system with price competition consisting of one manufacturer and one retailer in each supply chain under carbon cap-and-trade regulation. Considering vertical-horizontal cooperation, the six different models ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The optimal carbon emission reduction, pricing and social welfare were studied under four scenarios, non-cooperative decision making, local cooperative decision making I, local cooperative decision making II and comprehensive cooperative decision making, in a context in which the government imposes carbon tax on carbon emitters and consumers have environmental awareness. Zhang et al [8] studied the cooperative carbon emission reduction in a three-level supply chain system composed of manufacturers, transporters and retailers under the total carbon control and trading policy and consumers environmental awareness, and used the Stackelberg game to explore the optimal decision made by supply chain members in four cooperative decision models. This study showed that the scenario involving the full cooperation of all supply chain members performed the best in terms of carbon emission reduction, market equilibrium quantity, and supply chain system profit.…”
Section: Cooperation Strategies Between Supply Chain Enterprisesmentioning
confidence: 99%
“…The optimal carbon emission reduction, pricing and social welfare were studied under four scenarios, non-cooperative decision making, local cooperative decision making I, local cooperative decision making II and comprehensive cooperative decision making, in a context in which the government imposes carbon tax on carbon emitters and consumers have environmental awareness. Zhang et al [8] studied the cooperative carbon emission reduction in a three-level supply chain system composed of manufacturers, transporters and retailers under the total carbon control and trading policy and consumers environmental awareness, and used the Stackelberg game to explore the optimal decision made by supply chain members in four cooperative decision models. This study showed that the scenario involving the full cooperation of all supply chain members performed the best in terms of carbon emission reduction, market equilibrium quantity, and supply chain system profit.…”
Section: Cooperation Strategies Between Supply Chain Enterprisesmentioning
confidence: 99%
“…They considered that the cost for the emission is used within the system. Li et al [17] investigated CAPT policy for vertical and horizontal cooperation. They found that asymmetric competition changes the bargaining power of an SCM.…”
Section: Capt Policy and Carbon Emission Within The Scmmentioning
confidence: 99%